Zooplankton Composition of Karkamiş Dam Lake (Gaziantep-Turkey) - Aliş, Necla Ipek; Saler, Serap (Universitatea din Oradea, 2016)
Zooplankton of Karkamiş Dam Lake was investigated seasonally between April 2011 and May 2012 period. During the study, a total of 43 species (28 belong to phylum Rotifera, 10 to Cladocera and 5 Copepoda) were found in Karkamiş Dam Lake. All of the zooplanktonic species have been identified for the first time in Karkamiş Dam Lake. Some chemical and physical parameters as pH, dissolved oxygen, water temperature were measured during field trips. © Biharean Biologist, Oradea, Romania, 2016.
Keywords: Cladocera; Copepoda; Karkamişdam lake; Rotifera